Exploring Climate of the Euro‐Mediterranean Using a Variable‐Resolution Configuration of the Global Community Earth System Model (VR‐CESM) - Boza, Burcu; Herrington, Adam; Ilicak, Mehmet; Danabasoglu, Gokhan; Sen, Omer Lutfi (American Geophysical Union (AGU), 2025)
Abstract A Variable‐Resolution, global configuration of the Community Earth System Model (VR‐CESM) in which the atmosphere and land are the only active components is employed to investigate the climate of the Euro‐Mediterranean region. Two variable‐resolution grids with regionally refined resolutions of 0.25° and 0.125° over the study domain, respectively, are used. The fidelity of these VR‐CESM simulations is evaluated considering the near‐surface air temperature and precipitation fields for the 2000–2014 period in comparison to available observation‐based data sets and those of a coarse resolution (quasi‐uniform 1°) control simulation. Our analysis shows that, as a global model, VR‐CESM can be employed as an alternative to regional climate models to advance our understanding of the Euro‐Mediterranean climate. The improvements obtained are mainly related to a better representation of the complex topography of the region with higher resolution. Increasing the regional resolution to 0.25° generally yields considerable improvements over the control simulation; however, some persistent biases remain. Doubling the highest resolution to 0.125° leads to only modest improvements, primarily in the representation of small‐scale processes including representation of extreme events that are of substantial relevance for the present and future of the regional climate.